Approaches towards building the concept of “school pathways” - Briscioli, Bárbara (2017)
This article presents a conceptual perspective built on a doctoral dissertation on educational pathways, in a scenario where the compulsory period of secondary schooling has been extended in Argentina. First of all, sociological debates are discussed in an attempt to understand the multiple factors making up the subject’s life experiences. Arguments focus on how each of these factors are weighed, and suggestions are made to analyze the relationships between them. Secondly, educational pathways are referred to, drawing special attention to the institutional conditions that define them as they make up the concepts of what is standard. In turn, an attempt is made to show that subjects make their way through the educational system in a variety of ways. Thirdly, the transition from adolescence into youth is analyzed to add depth to the place secondary education has occupied in light of the population recently entering this level. Then, surveys on school dropout rates are analyzed in order to account for the prevailing ways in which this phenomenon is understood and to highlight the place school has as an institution. It is stated that standard schooling conditions create concrete, specific difficulties during the subjects’ passage through the secondary level. Finally, an outline is given of the issues to be taken into account when undertaking the conceptualization of educational pathways.